In-depth analysis of ultrasonic-induced geological pore re-structures - Tian, Leng; Wang, Hengli; Wu, Tao; Yang, Haien; Xu, Shuwen; Chai, Xiaolong; Zhang, Kaiqiang (Ultrasonics sonochemistry, 2022)
•Initial try to apply ultrasonics for manipulating in-situ geological pores.•Qualitative and quantitative characterizations of ultrasonics in pore restructures.•Guidance to apply ultrasonics in geo-energy production and energy storage. Understanding and manipulating geological pore structures is of paramount importance for geo-energy productions and underground energy storages in porous media. Nevertheless, research emphases for long time have been focused on understanding the pore configurations, while few work conducted to modify and restructure the porous media. This study deploys ultrasonic treatments on typical geological in-situ core samples, with follow-up processes of high-pressure mercury injections and nitrogen adsorptions and interpretations from nuclear magnetic resonance and x-ray diffraction. The core permeability and porosity are found to increase by 8.3 mD, from 4.1 to 12.4 mD, and by 0.95%, from 14.03% to 14.98%, respectively. Meanwhile, the number and size of the micro- and mesopore are increased with progressing of ultrasonic treatment, while those of the macropore decrease, which finally increase the permeability and porosity. The increase of micro- and mesopore number, from x-ray diffraction results, is attributed to the migration and precipitation of clay minerals caused through ultrasonic wave. The relocation of clay minerals also helps to improve the pore-throat connectivity and modify the micro-scale heterogeneity. Basically, this study reveals the characterizations of geological pore reconfigurations post-ultrasonic treatments and interprets the associated mechanisms, which provides guidance to manipulate the geological pores and be of benefit for further porous media use in science and engineering.